Cloning of three human multifunctional de novo purine biosynthetic genes by functional complementation of yeast mutations. - Schild, D (1990)
Functional complementation of mutations in the yeast Saccharomyces cerevisiae has been used to clone three multifunctional human genes involved in de novo purine biosynthesis. A HepG2 cDNA library constructed in a yeast expression vector was used to transform yeast strains with mutations in adenine biosynthetic genes. Clones were isolated that complement mutations in the yeast ADE2, ADE3, and ADE8 genes. The cDNA that complemented the ade8 (phosphoribosylglycinamide formyltransferase, GART) mutation, also complemented the ade5 (phosphoribosylglycinamide synthetase) and ade7 [phosphoribosylaminoimidazole synthetase (AIRS; also known as PAIS)] mutations, indicating that it is the human trifunctional GART gene. Supporting data include homology between the AIRS and GART domains of this gene and the published sequence of these domains from other organisms, and localization of the cloned gene to human chromosome 21, where the GART gene has been shown to map. The cDNA that complemented ade2 (phosphoribosylaminoimidazole carboxylase) also complemented ade1 (phosphoribosylaminoimidazole succinocarboxamide synthetase), supporting earlier data suggesting that in some organisms these functions are part of a bifunctional protein. The cDNA that complemented ade3 (formyltetrahydrofolate synthetase) is different from the recently isolated human cDNA encoding this enzyme and instead appears to encode a related mitochondrial enzyme.